Enhancement of Fe3O4/Au Composite Nanoparticles Catalyst in Oxidative Degradation of Methyl Orange Based on Synergistic Effect. Issue 9 (29th June 2017) - Gao, Qin; Xing, Yan; Peng, Mingli; Liu, Yongshuai; Luo, Zhiyi; Jin, Yanyan; Fan, Haiming; Li, Kebin; Chen, Chao; Cui, Yali
Abstract : Enhancement of Fe3 O4 /Au nanoparticles (Fe3 O4 /Au NPs) catalyst was observed in the oxidative degradation of methyl orange by employing H2 O2 as oxidant. To evaluate the catalytic activity of Fe3 O4 /Au nanoparticles, different degradation conditions were investigated such as the amounts of catalyst, H2 O2 concentration and pH value. Based on our data, methyl orange was degraded completely in a short time. The enhanced catalytic activity and increased oxidation rate constant may be ascribed to synergistic catalyst‐activated decomposition of H2 O2 to OH radical, which was one of the strong oxidizing species. Besides, Fe3 O4 /Au nanoparticles have exhibited satisfying recycle performance for potential industrial application. Abstract : The synergistic enhancement effect was observed in the oxidative degradation of Methyl Orange (MO) by employing Fe3 O4 /Au NPs as catalyst and H2 O2 as oxidant.